Spectral and quantum-chemical research of antipyrine derivatives of some rare earth elements complex compounds - N. S. Rukk; R. S. Shamsiev; V. V. Kravchenko; A. Yu. Skryabina; V. V. Zamalyutin (Тонкие химические технологии)
Data on the synthesis, IR-spectra, powder XRD studies as well as the results of quantum-chemical calculations for [Ln(AP)6]I3, [Ln(AP)6](ClO4)3 (Ln = Sc, Y, La–Nd, Sm–Lu; AP – antipyrine, C11H12N2O) are presented. It was demonstrated that coordination of the ligand takes place through an oxygen atom of the antipyrine carbonyl group. The calculated results (DFT/PBE/L11) are in good agreement with the experimental ones.